The impact of inter-observer variability on the accuracy, precision and utility of a commonly-used grassland condition index. (October 2020) - Goodenough, Anne E.; Carpenter, William S.; McTavish, Lynne; Blades, Bryony; Clarke, Emily; Griffiths, Shaun; Harding, Nadine; Scott, Rebekah; Walsh, Emily; Wilson, Louisa; Hart, Adam G.
Highlights: Inter-observer variability (IOV) is a major problem in ecological indicator systems. Substantial IOV occurred in grassland condition assessment using Veld Condition Index. In 44% of sites IOV caused potential deleterious management recommendations. We recommend focused training to overcome problems caused by IOV. Abstract: Inter-observer variability in ecological surveying can reduce the robustness and reliability of measures used to inform habitat management. Grassland management is important across southern Africa. The Veld Condition Index (VCI) is a technique that combines field data on the relative abundance of grasses identified during a standardised survey with knowledge of how different grass species respond to grazing. This allows calculation of an Ecological Condition Index (ECI) for a particular site. The ECI value is related to threshold values to indicate grazing pressure. Here, for the first time, the effects of inter-observer variation in trained surveyors on condition assessment and resultant management recommendations are examined. There was substantial and statistically significant inter-observer variation in ECI values, driven primarily by differences in the number of times an observer identified grasses within the sample transect as being one of the species listed in the "Decreaser" category of the standardised protocol (i.e. species that decrease with grazing). Variation was random with respect to observers rather than being due to systematic (and thus predicable and potentially correctable) differences between observers. In 44% of sites, inter-observer variation resulted in important differences in assessment of grassland condition because the assessment spanned outcome threshold categories. In such cases, this could result in unnecessary or detrimental management being recommended by some observers including inappropriate burning, needlessly translocating or culling herbivores, or failing to align herbivore populations to the carrying capacity with negative effects on both grazers and veld. We recommend that a cautious approach be taken in using VCI/ECI to inform management and that identification training be focused on species in the Decreaser ecological category that drive inter-individual variation in overall ECI.